2020
DOI: 10.3389/fcomm.2020.00066
|View full text |Cite
|
Sign up to set email alerts
|

Debating Resource-Driven Development: A Comparative Analysis of Media Coverage on the Pacific Northwest LNG Project in British Columbia

Abstract: In Canada, the provincial government of British Columbia has been keen on building an export-oriented liquefied natural gas (LNG) industry since 2011. This paper examines media coverage of the Pacific NorthWest LNG project (PNW), which was considered as the flagship proposal leading the BC LNG development, until its abrupt cancellation in July 2017. The paper explores the differences between public, commercial, and independent media in energy reporting by tracing how six Canadian media outlets covered the rise… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…Thus, despite the vulnerability of Canada’s resource-dependent economy exposed by the pandemic-induced energy market volatility, energy discourses in mainstream Canadian media continue to view decarbonization as a secondary concern compared to restoring pre-pandemic economic normalcy. This is consistent with previous research on climate change and media issue attention cycles (e.g., Chen 2020 ; Dusyk et al 2018 ; Stoddart et al 2021 ), which has found that prominent domestic and international political events frequently divert public attention away from climate change mitigation, notwithstanding the issue’s growing urgency. In the current case, the pro-bitumen narratives provided economic and political justifications for climate change denialism 2.0 (Buck 2021 , Tindall et al 2021 ).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Thus, despite the vulnerability of Canada’s resource-dependent economy exposed by the pandemic-induced energy market volatility, energy discourses in mainstream Canadian media continue to view decarbonization as a secondary concern compared to restoring pre-pandemic economic normalcy. This is consistent with previous research on climate change and media issue attention cycles (e.g., Chen 2020 ; Dusyk et al 2018 ; Stoddart et al 2021 ), which has found that prominent domestic and international political events frequently divert public attention away from climate change mitigation, notwithstanding the issue’s growing urgency. In the current case, the pro-bitumen narratives provided economic and political justifications for climate change denialism 2.0 (Buck 2021 , Tindall et al 2021 ).…”
Section: Resultssupporting
confidence: 91%
“…Notably, how decarbonization will affect the future of the domestic oil and gas sector has become an increasingly divisive issue in the Canadian public sphere, with the media playing a crucial role in mediating competing claims and narratives. This is evidenced by recent public controversies concerning mega Canadian fossil fuel projects (e.g., the Northern Gateway Pipeline project and the Pacific NorthWest Liquefied Natural Gas project), during which different news outlets disseminated relevant coverage that reflected competing stakeholder concerns (Chen 2020 ; Dusyk et al 2018 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…But overall, bridge fuel references in Canadian media remained low during 2016-2019. By comparison, during the same period Canadian national newspapers the Globe and Mail and the National Post alone produced more than 300 articles on the BC LNG controversy (Chen, 2020). Canadian media's lack of attention to bridge fuel presents a surprising finding, considering the country's continuing efforts on expanding fracking activities in recent years (see Thomas et al, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…Chen and Gunster (2016) analyzed pro-LNG information sources in British Columbia, Canada, and found two main themes: one emphasizing economic benefits and the other the “clean” nature of natural gas when compared to other fossil fuels, echoing some of the same frames found surrounding fracking. Examining media coverage specific to the Pacific LNG export project in British Columbia, Chen, 2020 again uncovered a framing contest pitting the economy versus the environment—this time stoked by pro-LNG forces and particularly prevalent in commercial media. Independent media outlets, instead, focused on environmental impacts of the proposed project, as well as fears about the industry’s influence over government decision-makers and democratic accountability, particularly as related to the rights of Indigenous peoples.…”
Section: Introductionmentioning
confidence: 99%